A collection of selected works of famous Ukrainian syntaxists - Khrystianinova, Raisa (Ukrainian linguistics, 2021)
The book review: Syntax of the Ukrainian language: textbook in 2 parts / A. Moisiienko, V. Chumak, S. Shevel eds. Kyiv : Publishing house “Kyiv University”, 2019. Information about the author: Raisa Khrystianinova – Dr Hab, Prof., Head of the Department of the Ukrainian Language; Zaporizhzhya National University (Ukraine). E-mail: khrystianinova@gmail.com